2005
DOI: 10.1128/jvi.79.24.15226-15237.2005
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of HLA-G Expression in Human Neural Cells after Neurotropic Viral Infections

Abstract: HLA-G is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
87
0
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 115 publications
(98 citation statements)
references
References 81 publications
5
87
0
6
Order By: Relevance
“…HLA-G has been suggested to participate in the escape of viruses from the immune response generated by the nervous system. 40 We previously observed an increase of HLA-G transcripts in the brain of VEEV-exposed nonhuman primates, and we see it in the present study in the naïve or vaccine responders PBMCs but not in the vaccine nonresponder group. 19 its transcription activator (i.e., PF4 and USF1) and a natural killer receptor that recognizes MHC class Ia and Ib molecules (CD160) were among the top biomarkers for the vaccine nonresponder group.…”
Section: Discussionsupporting
confidence: 71%
“…HLA-G has been suggested to participate in the escape of viruses from the immune response generated by the nervous system. 40 We previously observed an increase of HLA-G transcripts in the brain of VEEV-exposed nonhuman primates, and we see it in the present study in the naïve or vaccine responders PBMCs but not in the vaccine nonresponder group. 19 its transcription activator (i.e., PF4 and USF1) and a natural killer receptor that recognizes MHC class Ia and Ib molecules (CD160) were among the top biomarkers for the vaccine nonresponder group.…”
Section: Discussionsupporting
confidence: 71%
“…Both are associated with 2 microglobulin [22]. HLA-G, which was originally thought to be present exclusively in the human placenta [23,24] has also been detected in brain and neural cells [25,26] including human neurons [8].…”
Section: Introductionmentioning
confidence: 99%
“…One such molecule, the Ligand of Fas, FasL, has been shown to be involved in the killing of migratory T cells into the nervous system (NS) in rabies virus (RABV) infection [2,3]. HLA-G, a non classical MHC molecule which expression in cells is up regulated following infection with human cytomegalovirus (HCMV), human immunodeficiency virus (HIV-1) and RABV could also contribute by a similar mechanism to the immunoevasion of these viruses [4][5][6][7][8]. In addition, HIV-1 and HCMV up regulate the expression of another non classical MHC class I molecule,…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the cytokines that is highly expressed in RPE cells is IFN-␤. Induction of Type 1 IFN gene expression is an essential component of innate immunity (22,23). Recent studies (24) have also shown that neurons produce high levels of IFN-␤ through TLR 3 signaling.…”
mentioning
confidence: 99%